THE ROLE OF PARASITOIDS AND PREDATORS FOR CONTROLLING COTTON LEAFHOPPER Amrasca biguttula (ISHIDA) (HETEROPTERA: CICCADELIDAE) - . NURINDAH (Perspektif, 2012)
Cotton leafhopper, Amrasca biguttula is a serious early-season cotton pest. It sucks plant sap, injects its toxic saliva, and causes hopper burn. Controlling the cotton leafhopper with aerial spray of insecticides causes another problem i.e., increasing population of cotton bollworm, Helicoverpa armigera as its natural enemies are also eliminated. So far, released-national-cotton varieties have been moderately resistant to the leafhopper and will not survive when the pest population is high. The use of systemic insecticide, through seed treatment before planting, could escape the leafhopper damage symptom until 60 days after planting, negatively affects to the development of natural enemies, and long term usages may cause damages to the environment. Indigenous parasitoids and predators can be used for controlling the leafhopper population effectively, efficiently, and environmentally friendly. The predominant parasitoids on cotton plantation are egg parasitoids, Anagrus spp., and predators are spiders, lady bird beetles, and predatory mired bugs. The role of parasitoids and predators could be optimized by increasing their population in the early season. This could be done by addition of their food sources through raising the vegetation diversity, spraying foods for predators and attractant for parasitoids and predators. Intercropping cotton with secondary food crops would increase vegetation diversity, increase predator population, and egg parasitism. It may also suppress the leafhopper population, maintain cotton-seed productivity, and leave out chemical insecticide spray.Key words: Amrasca biguttula, cotton, cotton leaf-hopper, parasitoid, predator.